Peaceful Entry, Tolerant Mentality: The Perception of the Citizens of the Muslim World on Indonesian Islam - Suryana, Yayan; Rosadi, Andri; Andayani, Andayani; Fithriya, Dwi Nur Laela; Muthahari, Nisrina (FIKRAH, 2026)
Indonesia is home to the world’s largest Muslim population. Yet, it is also the youngest major Islamic civilization, the farthest from the historical centers of the Muslim world. It is often perceived as the least authoritative in matters of Islamic knowledge and practice. The flow of religious information and scholarly authority in the global Islamic ecumene has historically moved from the center—the Arab heartlands, Persia, and Anatolia—toward the periphery, with remarkably little reciprocal knowledge flowing in the opposite direction. This article examines how citizens of four Muslim-majority nations—Iran, Pakistan, Egypt, and Turkey—perceive Indonesian Islam. Drawing on interview data with scholars, educators, analysts, and informed citizens from these four countries, they uncover the perceptions of the citizens of the centers of the Islamic world on Indonesian Islam: the historically peaceful arrival of Islam in the Indonesian archipelago through commerce and Sufism rather than military conquest and the resulting contemporary character of moderation, tolerance, and pluralism. The respondents’ answers are substantially accurate, though not detailed. This article is intended to provide a view on the patterns and characters of Islam that developed in the world outside the Middle East, such as Indonesia.